Prunus lusitanica L. Fruits as a Novel Source of Bioactive Compounds with Antioxidant Potential: Exploring the Unknown - Ana Santos Abraão; Nelson Fernandes; Amélia M. Silva; Raúl Domínguez-Perles; Ana Barros (MDPI AG, 2022)
Prunus lusitanica L., also known as Portuguese laurel or locally known as 'azereiro', is a rare species with ornamental and ecological value. Only two studies regarding the bioactivity and chemical composition of its leaves were reported to date. Thus, the present study aims to qualitatively and quantitatively evaluate the phenolic profile, through HPLC-PAD-ESI-MS/MS (high-performance liquid chromatography-photodiode array detection-electrospray ionization tandem mass spectrometry), as well as the radical scavenging capacity, through ABTS (2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) and DPPH (2,2-diphenyl-1 picrylhydrazyl), and the reducing power (FRAP, ferric reducing antioxidant power) assays, of P. lusitanica fruits during a 4-year study. In total, 28 compounds were identified and quantified in the fruits, including 21 hydroxycinnamic acids (60.3%); 2 flavan-3-ols (27.9%), 2 anthocyanins (10.5%), 2 flavonols (1.0%), and 1 secoiridoid (0.3%). High antioxidant capacity was observed, with ABTS values ranging from 7.88 to 10.69 mmol TE (Trolox equivalents)/100 g fw (fresh weight), DPPH values from 5.18 to 8.17 mmol TE/100 g fw, and FRAP values from 8.76 to 11.76 mmol TE/100 g fw. According to these results, it can be concluded that these are rich sources of phenolic compounds with very promising antioxidant capacity and, therefore, with potential applications in the food and/or phytopharmaceutical sectors.